Sa mata ng isang bata a campaign exploring the small traumas children ages 5-8 experience from disciplinary scare tactics done by authoritative figures through a short film that exemplifies irrational and disruptive fear from their narrative - Juan, Ma. Marielle Jenikka A.
When children are rowdy or difficult to control, there are parents and caregivers who resort into using scare tactics to discipline them. In some cases, superstitious beliefs also get interspersed into this technique. While scare tactics may be effective in disciplining the children, this results into small traumas for them, which can develop into something more serious as they grow older. The problem itself lies in the way these small traumas are treated lightly, because not only does this interfere with a child's ability to fend for themselves, it also proves to be disruptive in the matters of action and thought. Small traumas are defines as small insignificant events that stick to a person's mind, which have the ability to distract and meddle with their thoughts as they go about their day. Small traumas can lead a person to develop trauma response symptoms, such as obsession over these thoughts or avoidance. A person who experiences small traumas feel more distressed and have a decreased quality of life. For the most part, gathered from the insights of the research, most parents and caregivers treat these scare tactics as disciplinary techniques that should not be taken seriously. However, more attention must be put into this because at a young age, children are still developing and learning about the environment around them. While they are able to distinguish fantasy and reality, these two things still come together and they are more likely to entertain fantastical thoughts. This research aims to educate the parents and the household helpers about how disruptive small traumas can be to children, specifically taken from a common scare tactic that every parent knows of. Although these fears may seem irrational, it still feels real to the children. Both the parents and caregivers should be conscious enough about imposing these kinds of scare tactics onto the children, given the consequences of small traumas and how they lead to pronounced anxiety, tension, and current fears. Instead of giving the children ways to adapt to small traumas they may already have, the research aims to tackle the roof of the problem by illustrating irrational and disruptive fear through a short film that exemplifies this, as well as challenging safe spaces from a child's narrative.